The effects of vertical vs. horizontal plyometric training on sprinting kinetics in post peak height female student athletes - Talukdar, K.; Harrison , C.; McGuigan, M.; Borotkanics, R. (International Journal of Strength and Conditioning, 2022)
Plyometric training is a form of jump training that is a useful method to improve sprinting speed due to its propensity to improve neural efficiency, increase joint stiffness and contraction speed. While research has shown that plyometrics can improve jumping and sprinting performance, no studies have compared the effects of different types of plyometric training on sprinting speed in young females. Therefore, the aim of the study was to compare different forms of plyometric training (horizontal and vertical) on sprinting performance in young females. Thirty young females from a private girls college were randomly divided into two groups and trained for seven weeks, twice a week; vertical plyometric (n=11, age 13.50 ± 0.96, peak heigh velocity-PHV: 1.60 ± 1.14), horizontal plyometric training (n=10, 13.40 ± 0.92, PHV:1.60 ± 0.93), and a physical education class as a control (n=15, age, 15.60 ± 0.31, PHV: 2.90 ± 0.55). Participants were tested for sprinting kinetics i.e. force (Fo), maximum power (Pmax), theoretical velocity (Vo), maximal velocity (Vmax), 10, 20 and 30 m split times using a radar gun over 30 m, isometric strength, vertical jump height and horizontal jump distance before and after the intervention. Both the intervention groups significantly improved all performance variables (g= 0.32- 1.30; p<0.05). The vertical group improved all kinetic variables except Fo and Pmax whereas the horizontal group improved all kinetic variables with a greater effect size g= 0.40-1.30. In comparison to the control group, the vertical group significantly improved Vo, Vmax, vertical and broad jump scores whereas the horizontal group significantly improved broad jump and 20 m split time scores (p<0.05). The findings of this study suggest that horizontal plyometric training is more effective in improving sprinting kinetics.